Pengaruh Work Life Balance dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Kantor Camat Raba Kota Bima - Nurlaeli, Nurlaeli; Haryanti , Intisari; Muhajirin, Muhajirin (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to determine and analyze the influence of work-life balance and work environment on employee performance at the Raba Subdistrict Office, Bima City, both partially and simultaneously. This research employed a quantitative method with an associative approach. The population consisted of 33 employees, while the sample comprised 30 respondents selected using purposive sampling. Data were collected through observation, questionnaires, and literature review. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, t-test, and F-test. The results showed that work-life balance has a positive and significant effect on employee performance, with a t-count of 3.266 > t-table of 2.023 and a significance value of 0.002 < 0.05. The work environment also has a positive and significant effect on employee performance, with a t-count of 3.071 > t-table of 2.023 and a significance value of 0.004 < 0.05. Simultaneously, work-life balance and work environment have a significant effect on employee performance, with an F-count of 50.034 > F-table of 4.09 and a significance value of 0.000 < 0.05. The correlation coefficient of 0.854 indicates a very strong relationship, while the coefficient of determination (R²) of 0.730 indicates that 73.0% of the variation in employee performance can be explained by work-life balance and work environment, while the remaining 27.0% is influenced by other factors not examined in this study. Therefore, improving work-life balance and creating a conducive work environment can contribute to improving employee performance at the Raba Subdistrict Office, Bima City.